The role of causal reasoning in children’s social inferences about leaders - Yılmaz, Duygu. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
Attributional processes influence children’s status-based attitudes. Children approach high-status individuals more positively when the status is attributed to internal factors. The present aimed to understand the influence of different causal attributions (internal vs. external) on 6-7-years-old and 9-10-years old children’s attitudes toward leaders by comparing two leaders who attained equally high statuses due to different causes. Parental education of the children was also examined to understand its role in children’s attributional processes and status-based judgments. Children (N = 64) saw two presidents, one of whom became a president due to internal reasons, and one due to external reasons. Children were asked how much they supported presidents and to infer presidents’ intelligence and success in their roles. Finally, children were asked whether they expected these presidents to become presidents in different contexts as well. Both younger and older children thought leaders who attained their position due to internal factors (vs. external factors) were more successful and intelligent, and the difference was larger for older children. Older children supported leaders with internal explanations more than leaders with external explanations but younger children’s support for the leaders did not differ based on causal attributions. Furthermore, as parental education increased, children tended to support leaders less. Older children thought that leaders who attained their role due to internal factors would be more likely to have a leadership position also in different cities, while younger children were at chance level. Moreover, as parental education increased, children were more likely to attribute less stability to the leadership status of the leaders with external explanations. Overall, results revealed that children’s evaluations of leaders interact with attributional processes and contextual factors throughout their development.
Keywords: Social influence.; Leadership.